False‐negative detections from environmental DNA collected in the presence of large numbers of killer whales (Orcinus orca). Issue 4 (12th September 2019) - Pinfield, Róisín; Dillane, Eileen; Runge, Anne Kathrine W.; Evans, Alice; Mirimin, Luca; Niemann, Jonas; Reed, Thomas E.; Reid, David G.; Rogan, Emer; Samarra, Filipa I. P.; Sigsgaard, Eva Egelyng; Foote, Andrew D.
Abstract: While environmental DNA (eDNA) is becoming increasingly established in biodiversity monitoring of freshwater ecosystems, the use of eDNA surveys in the marine environment is still in its infancy. Here, we use two approaches: targeted quantitative PCR (qPCR) and whole‐genome enrichment capture followed by shotgun sequencing in an effort to amplify killer whale DNA from seawater samples. Samples were collected in close proximity to killer whales in inshore and offshore waters, in varying sea conditions and from the surface and subsurface but none returned strongly positive detections of killer whale eDNA. We validated our laboratory methodologies by successfully amplifying a dilution series of a positive control of killer whale DNA. Furthermore, DNA of Atlantic mackerel, which was present at all sites during sampling, was successfully amplified from the same seawater samples, with positive detections found in ten of the eighteen eDNA extracts. We discuss the various eDNA collection and amplification methodologies used and the abiotic and biotic factors that influence eDNA detection. We discuss possible explanations for the lack of positive killer whale detections, potential pitfalls, and the apparent limitations of eDNA for genetic research on cetaceans, particularly in offshore regions. Abstract : Targeted quantitative PCR (qPCR) and whole‐genome enrichment capture of genomic eDNA libraries were carried out in an effort to amplify killer whale DNA in seawater samples collected in close proximity to killer whales in the North Atlantic. However, none returned strongly positive detections of killer whale DNA. We validated our methods by successfully amplifying positive controls of DNA extracted from killer whale blood, and we also amplify Atlantic mackerel DNA from the same seawater samples. We conclude that killer whale DNA was either absent or present in quantities too low to unequivocally confirm species presence, despite positive close‐range visual detections.